2016
DOI: 10.1088/0965-0393/24/5/055012
|View full text |Cite
|
Sign up to set email alerts
|

A micro-mechanical analysis of thermo-elastic properties and local residual stresses in ductile iron based on a new anisotropic model for the graphite nodules

Abstract: In this paper, the thermo-elastic behavior of the graphite nodules contained in ductile iron is derived on the basis of recent transmission electron microscopy investigations of their real internal structure. The proposed model is initially validated by performing a finite element homogenization analysis to verify its consistency with the room-temperature elastic properties of ductile iron measured at the macro scale. Subsequently, it is used to investigate the formation of local residual stresses around the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 48 publications
1
40
0
2
Order By: Relevance
“…In the equatorial area, some traces of the superficial destruction of the spheroid structure in the form of parallel shifted graphene layers, were revealed in the radial sectors (Figure c,d). Such a displacement of graphene layers could be caused by the local tangential stress effect on the superficial shield of the graphite nodule, mentioned by Andriollo et al (). This effect was active when the graphite nodule was finally pulled out from the matrix.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…In the equatorial area, some traces of the superficial destruction of the spheroid structure in the form of parallel shifted graphene layers, were revealed in the radial sectors (Figure c,d). Such a displacement of graphene layers could be caused by the local tangential stress effect on the superficial shield of the graphite nodule, mentioned by Andriollo et al (). This effect was active when the graphite nodule was finally pulled out from the matrix.…”
Section: Resultsmentioning
confidence: 97%
“…Thus, the models of the microstructural determination of damage course in the spheroidal cast iron were extended to a discrete approach. The local stress field at the G/M interface around a graphite spheroid embedded into metal matrix was analyzed and recognized as a factor involved in the material damage (Andriollo, Thorborg, Tiedje, & Hattel, ; Bonora & Ruggiero, ; Di Cocco, Iacoviello, Rossi, & Iacoviello, ; Fukumasu, Pelegrino, Cueva, Souza, & Sinatora, ; Zhang et al, ). Furthermore, the obtained results showed that graphite could not be considered as an isotropic phase.…”
Section: Introductionmentioning
confidence: 99%
“…The different DCIs mechanical properties, such as, high values of tensile strength and Young's modulus, among others [7], are some of the reasons that make DCIs very versatile for different engineering fields such as the automotive industry, mining industry, among others [8,9]. To perform the analysis of the mechanical properties, it is necessary to use computational tools, such as the Finite Element Analysis (FEA), which allows for relating the mechanical behavior with the microstructural properties of the DCI [10,11]. In order to obtain adequate results through the FEA, it is necessary to develop models that represent the geometry of the DCI as closely as possible to the real geometries (or to that established by studies concerning nodule sphericity), since models with incorrect approximations, which can show very pronounced or irregular graphite nodules contours, can generate stress concentrators that will lead in practice to an incorrect estimation of the mechanical properties in the FEA simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the models that consider graphite nodules as holes, despise the effects on the mechanical properties of graphite in the microstructure of DCIs. On the other hand, other works have used models where the graphite nodules are not considered as holes, but as ideal spheres of graphite, with the aim of making a thermoelastic formulation of the internal structure of graphite nodules to verify the elastic behavior of a DCI by means of an FEA [10]. At this point, the works that are mentioned above have only used geometric models where nodules are considered as holes or ideal spheres.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding SGI, the most common way has been to use a unit-cell approach due to the favourable symmetry of a spheroidal graphite particle [31,105,106,[115][116][117][118][119][120]. In this approach, the RVE is modelled as a cubic or cylindrical cell in which a spherical graphite particle or void is situated.…”
Section: Constitutive Modellingmentioning
confidence: 99%